Broccoli various genotypes regenerated plants (R0) seed set after geitonogamy - E. A. Zablotskaya; A. I. Mineykina; E. A. Domblides; T. O. Paslova; L. L. Bondareva (Овощи России, 2020)
Relevance. Broccoli cabbage (Brassica oleracea L. convar. botrytis (L.) Alef. var. cymosa Duch.) is widely spread around the world due to its dietetic attribute, preventive and healing effect, cooking simplicity. F1 hybrids production is the main stream in modern crop breeding as they surpass varieties in evenness and yield quality. However, it takes up to 6 years of inbreeding to obtain pure parent lines capable for hybrid creation. Thus biotechnological methods, especially doubled haploids production technology shell be implemented in selection process. 100% homozygous line can be worked out in one generation by this technology. Nevertheless earlier researches revealed such plants low seed set that hinder their application in mass production. Therefore after pollination seed set level identification is an important step in applying lines gained via in vitro process.Materials and methods. Broccoli cabbage regenerated plants produced by isolated microspore in vitro culture method were used as raw material in our study. Flower and bud pollination was held in climate cells.Results. Study of 11 broccoli cabbage DH-lines disclosed genotype influence the ability to set seeds after bud pollination. 93.3% genotype A and 95.5% A1.3 pods were seedless in our experiments. Most genotypes demonstrated 50.3-85.7% seed set level. Low and middle ability to form seeds prevailed mainly. This peculiarity should be considered while dealing with regenerated plants by raising the number of crossings for successful breeding.